The Effect Of Brand Image And Electronic Word Of Mouth (E-Wom) On Purchase Decisions For Labore Products In Bandar Lampung - Stefany Crisnia Gunawan; Dorothy Rouly Haratua Pandjaitan; Nuzul Inas Nabila (Cita konsultindo, 2026)
This research is motivated by the growing beauty industry in Indonesia and the increasing public awareness of the importance of skin health and care. This study aims to analyze the influence of brand image and electronic word-of-mouth on purchasing decisions for Labore products in Bandar Lampung. This research uses a quantitative approach with a non-probability sampling technique, specifically purposive sampling. Data was collected by distributing questionnaires to 200 social media users who had previously purchased or used Labore products. Data analysis was performed using multiple linear regression with the assistance of SPSS software version 27. The research results indicate that both brand image and electronic word-of-mouth have a positive and significant influence on the purchase decision for Labore products in Bandar Lampung. This proves that the stronger the brand image and the more positive the consumer reviews on social media, the higher the consumer's decision to purchase the product. This research has implications for companies to strengthen their brand communication strategies and optimize E-WOM in increasing consumer purchasing decisions in the local skincare market.